Alcohol dependence of anode-selective electrophoretic deposition of non-ionic poly(ester–sulfone). (6th April 2016) - Yokoyama, Mizuki; Takasu, Akinori
Abstract: Poly(ester–sulfone) was synthesized via a thiol-ene click reaction between bis(butenyl) methylsuccinate and 1, 4-butanedithiol, and the product poly(ester–sulfone) was found to move to the anode selectively in electrophoretic deposition (EPD) on stainless steel. To clarify the electrophoretic mechanism, dispersions consisting of poly(ester–sulfone) and various protic solvents were prepared, and EPD on a metal substrate (stainless steel, titanium, indium tin oxide (ITO), zinc, and platinum) was performed. When an aprotic polar solvent ( N, N -dimethylformamide, N, N -dimethylacetamide, and dimethyl sulfoxide) was used as the good (soluble) solvent and various alcohols as the poor (insoluble) solvent, anode-selective EPD behavior was attained. The negative zeta potential of each dispersion (−40 to −20 mV) was also confirmed, again using various alcohols as the poor solvent, which reveals that the electrophoretic behavior is dependent upon a partial charge separation in the protic solvent (alcohol) at the interface of the dispersion. Graphical abstract: